The Industrial Heritage of the City of Malaga: Analysis of Its Current Situation and Support for Its Activation as a Resource for Urban Development - Alba-Dorado, María Isabel (MDPI, 2022)
This article forms part of the debate regarding the relevance of using industrial heritage as an engine for territorial and urban development. It begins by studying the concept of industrial heritage and recognition of the same as cultural heritage and, subsequently, using the city of Malaga as a case study, analyses the industrialisation process that the city experienced from the 19th to the end of the 20th century and the current state of conservation of its built industrial heritage. It also undertakes a study of the specific instruments, for the most part strategic planning, that have been implemented as a means to incorporate cultural heritage as an asset for a new urban model for the city in an effort to understand how these instruments envisage the revitalisation and recovery of industrial heritage. The study concludes that this heritage, despite constituting one of the city’s principal hallmarks, has received only partial and biased attention in terms of the numerous urban reclassification projects that have been undertaken, and has yet to find its role in the new urban model. This raises the need to revitalise these heritage resources in an effort to encourage fairer, more equitable urban and economic development processes that contemplate the reasonable use of the industrial heritage that constitutes the bedrock of the city’s identity.
Keywords: Desarrollo urbano; Industrial heritage; Urban development; Strategic planning; Malaga